(untitled) (Novateur Publications, 2023)
The formulation of the problem in this study is whether there is an effect of applying the commando teaching style to improving learning outcomes in freestyle swimming? This study aims to examine the application of the commando teaching style to improving learning outcomes in freestyle swimming. The method used in this research is the experimental method. The sample used was students of SMA Negeri I Tondano for the 2022/2023 academic year, totaling 20 samples, which were divided into two groups, namely the experimental group with a commando teaching style totaling 10 samples and the control group which did not receive treatment totaling 10 samples. for one month with a frequency of three times a week. The research design used was "Randomized control group pre-test and post-test design. "The instrument used in this study was the "25 meter freestyle swimming speed test." The data collection technique in this study was to conduct an initial test and a final test in the 25 meter freestyle swimming for both groups. The research hypothesis is "The application of the command teaching style has an influence on improving learning outcomes in the 25- meter freestyle swimming at SMA Negeri I Tondano." The data analysis technique used is the t-test statistical analysis technique, before the t-test is carried out, it begins with testing the analysis requirements, namely the data normality test and the variance homogeneity test. From the calculation of the research hypothesis testing, it is obtained that tcount is 8.75. Based on the t distribution table at ∝ 0.05 with degrees of freedom n1 + n2-2 = 10 + 10 – 2 = 18, a ttable of 2.101 is obtained. So tcount is bigger than ttable, that is tcount = 8.75 > ttable = 2.101. Based on the test criteria, if tcount is greater than ttable (tcount > ttable) then Ho is rejected, which means HA is accepted. The results of this study indicate that the average increase in learning outcomes in freestyle swimming in the experimental group using the commando teaching style is better than the average increase in learning outcomes in freestyle swimming in the control group which does not receive treatment. The conclusion of this study is that there is an effect of applying the commando teaching style to improving learning outcomes in 25-meter freestyle swimming in SMA Negeri I Tondano.